Book Review: Hollowing Out the Middle: The Rural Brain Drain and What It Means for America - Hobart L. Harmon (Journal of Research in Rural Education, 2010)
Hollowing out the Middle represents what should be a critically influential study for guiding education reform in rural America. Using survey data from 275 former high school students, in-depth interviews with more than 100 young adults across the nation who attended the high school in the late 1980s and early 1990s, coupled with intensive community-level fieldwork, the husband-wife team of sociology professors, Patrick Carr and Maria Kefalas chronicle the "coming-of-age" experiences of youth who formerly attended high school in "Ellis," Iowa. In the process they uncover how a high school and its community inadvertently contribute to the brain drain and "hollowing out" of a small town in America's heartland.